IRON REDUCTION AND SOIL PHOSPHORUS SOLUBILIZATION IN HUMID TROPICAL FORESTS SOILS: THE ROLES OF LABILE CARBON POOLS AND AN ELECTRON SHUTTLE COMPOUND - Chacon N.; Silver W.L.; Dubinsky E.A.; Cusack D.F. (My University, 2006)
The affinity of iron oxides and hydroxides for phosphorus is thought to contribute to phosphorus limitation to net primary productivity in humid tropical forests on acidic, highly weathered soils. Perennially warm, humid conditions and high biological activity in these soils can result in fluctuating redox potential that in turn leads to considerable iron reduction in the presence of labile carbon and humic substances. We investigated the effects of reducing conditions in combination with the addition of labile carbon substrates (glucose and acetate) and an electron shuttle compound on iron reduction and phosphorus release in a humid tropical forest soil. Glucose or acetate was added to soils as a single dose at the beginning of the experiment, and as pulsed inputs over time, which more closely mimics patterns in labile carbon availability. Iron reduction and phosphorus mobilization were weakly stimulated by a single low level addition of carbon, and the addition of the electron shuttle compound with or without added carbon. Pulsed labile carbon additions produced a significant increase in soil pH, soluble iron, and phosphorus concentrations. Pulsed labile carbon inputs also promoted the precipitation of ferrous hydroxide complexes which could increase the capacity for P sorption, although our results suggest that rates of P solubilization exceeded re-adsorption. Plant and microbial P demand are also likely to serve as an important sinks for released P, limiting the role of P re-adsorption. Our results suggest that reducing conditions coupled with periodic carbon inputs can stimulate iron reduction and a corresponding increase in soil phosphorus mobilization, which may provide a source of phosphorus to plants and microorganisms previously undocumented in these ecosystems.
Keywords: ACETATE; ANAEROBIC SOILS; AQDS; GLUCOSE; HIGHLY WEATHERED SOILS; NUTRIENT CYCLING; PHOSPHORUS LIMITATION; SOIL REDOX